PERBEDAAN KELUHAN NYERI PUNGGUNG PADA SISWA KELAS V ANTARA SD X DAN SD Y AKIBAT PENGGUNAAN TAS PUNGGUNG DI TEMBALANG - Rizqi Haidar; Baju Widjasena; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Prevalence of backpain due to backpack usage is increasing to elementary school students. Heavy load, backpack usage duration and the way to bring the load which has to be brought is several factors that causing back pain complaint. This research is purposed to know the difference of back pain complaint between 5th grade students in X elementary school and Y elementary school due to backpack usage in Tembalang. This research is using survey analitic design with cross sectional appoach. There are 3 instruments, which are measurement by using analog scale to measure students body weight, micro toa to measure students tall, and enquette filling to know the exixtence of back pain complaint in students. The population was 5th grade students in X elementary school and Y elementary school, amounting to 123 elementary school students. Samples were taken using total sampling method that met the inclusion criteria, amounting to 112 students. The result shows that in X elementary school there are 31,1% moderate back pain, 54% mild back pain and 14,8% without back pain. While in Y elementary school there are 3,9% severe back pain, 66,7% moderate back pain, 25,5% mild back pain, and 3,9% without back pain. This data are analysed by using Mann-Whitney Use until got significance value (p-value=0.000) which mean there is difference backpain complaint between 5th grade students in X elementary school and Y elementary school due to backpack usage in Tembalang. Suggestion for school is to serve safety locker to each students.